Application of mind mapping in quality management of nursing records in the Emergency Department (思维导图在急诊病房护理文书书写质量管理中的应用) - SHI Hailiu (施海柳); CHEN Jiachun (陈佳春) (Association of Integrative Nursing, 2022)
Objective To investigate the effect of mind mapping in improve the quality of writing nursing records in the Emergency Department. Methods A total of 100 copies of nursing records were collected as control group before implementation of mind mapping management (from Jan to June 2021). The mind mapping had been introduced in the quality management of nursing records since July 20 21, and 100 copies of nursing records were collected as observation group before implementation of mind mapping management (from July to December 2021). The rate of disqualified nursing records was compared between two groups. Results The rate of disqualified nursing records was 2. 00%(2/100) in the observation group, which was significantly lower than 16. 00%(16/100) in the control group (P＜0. 01). Conclusion The mind mapping, as an logical and well-organized toll, is potentially effective to improve the quality of nursing records in the Emergency Department. (目的 探讨运用思维导图提升急诊病房护理文书书写质量的效果。方法 收集 2021年1月-6月急诊病房护理文书100份为对照组。2021年7月科室运用思维导图提升护理文书书写质量管理, 收集2021年7月-12月急诊病房护理文书100份为观察组。对比分析两组护理文书书写质量。结果 观察组护理文书书写不合格率2. 00%(2/100), 低于对照组的16. 00%(16/100), 差异有统计学意义(P＜0. 01)。结论 思维导图具有层次分明、条理清晰的特点, 可以提升急诊病房护理文书书写质量。)